The Black Underclass Concept: Self-Help vs. Government Intervention - Carson, Emmett D. (American Economic Review, 1986)
The concept of an American underclass has become the subject of increasing discussion. Although the term does not enjoy a precise definition, most researchers acknowledge that the underclass condition involves more than being cash poor. Members of the underclass are also believed to have attitudinal and behavioral deficiencies. Other terms that have been used to describe this group over the years include: dangerous classes, other Americans, culture of poverty, and lower classes (see Ken Auletta, 1981). Within this area of inquiry, several researchers have chosen to study what has been termed the black underclass. The purpose of this paper is twofold. First, the appropriateness of the data that are used to characterize members of the black underclass will be examined. Second, the argument that perhaps the most viable solution to the problems of the black underclass are community self-help programs, rather than government programs, will be discussed.